Fully self-powered electrocaloric cooling/heating with triboelectric nanogenerator. (October 2022) - Li, Jiayu; Liu, Boxun; Liang, Chuangjian; Wan, Lingyu; Wei, Wenjuan; Gao, Hongqiang; Li, Mingyang; Li, Yahui; Ding, Wangyang; Qu, Hang; Wen, Honggui; Yu, Fang; et al.
Abstract: The annual energy consumption to supply traditional power for cooling or heating applications is tremendous. Refrigeration or heating technology that does not rely on traditional energy sources is of great interest for modern society to achieve energy conservation and emission reductions. In this work, we demonstrated a self-powered cooling and heating system, consisting of a triboelectric nanogenerator (TENG), a power and charging management module, and an electrocaloric (EC) material. Ferroelectric ceramics of 0.1 PbTiO3 –0.9 PbSc0.5 Ta0.5 O3 (PSTT) with high EC at room temperature were successfully prepared. By converting the TENG-harvested kinetic energy of the mechanical motion into electrical energy and applying or releasing a polarized electric field to 12 PSTT sheets through circuit management, we achieved excellent dual self-powered cooling/heating functions in the room-temperature range. When the operating frequency of the TENG was 3 Hz, in a space with a specific surface area ratio of only 3.328 % and a volume ratio of 0.433 %, a temperature change of 0.5 K was achieved within 5.5 min, and the energy conversion efficiency reached 10.926 %. Because the TENG can effectively harvest the kinetic energy of various motions, including body motions and widely distributed wind, water wave, and raindrop energy in nature, it can be used to develop compact, miniaturized, and self-powered solid-state cooling/heating devices based on the EC effect. With the advantages of a high coefficient of performance, ease of use, zero emissions and lack of pollution production, our proposed approach is expected to achieve widespread application in various fields. Graphical abstract: Using a TENG to harvest and convert energy into electrical energy, which provides a polarized electric field to PSTT through the circuit management. In a confined space, with an area ratio of 1:30 and a volume ratio of 1:231 between the PSTT and the surrounding space, a temperature change of 0.54 °C was achieved in 5.5 min with an energy conversion rate of 10.926 % for the TENG with an area of 100 cm2 operating at 3 Hz. This is conductive to great application prospects. ga1 Highlights: The experiment successfully prepared PSTT ceramics with high electrocaloric effect at room temperature. The combination of ferroelectric materials and TENG has been reported for the first time to realize temperature change. The application achieved a temperature change of 0.54 °C in 230 times the volume of PSTT ceramics. This report provides a feasible solution for artificial quantitative temperature control under no-electricity conditions.